2018
DOI: 10.31449/inf.v42i3.1497
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Particle Swarm Optimization and Differential Evolution based Test Data Generation Algorithm for Data-Flow Coverage using Neighbourhood Search Strategy

Abstract: Meta-heuristic search techniques, mainly Genetic Algorithm (GA), have been widely applied for automated test data generation according to a structural test adequacy criterion. However, it remains a challenging task for more robust adequacy criterion such as data-flow coverage of a program. Now, focus is on the use of other highly-adaptive meta-heuristic search techniques such as Particle Swarm Optimization (PSO) and Differential Evolution (DE). In this paper, a hybrid (adaptive PSO and DE) algorithm is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Each SI technique has its own unique properties and will have different effects in different application scenarios. In recent years, in order to improve the performance of various SI techniques, and further improve the quality of the solution, various hybrid SI techniques: PSO-ACO [112]- [114], ACO-ABC [115], [116], DE-ABC [117], [118], FA-DE [119], PSO-DE [120], [121] and other hybrid SI algorithms [122], [123] are proposed and successfully applied in various fields. Reference [112] proposes a two-stage hybrid swarm intelligence optimization algorithm, using the randomicity, rapidity and wholeness of PSO and GA for rough searching; and for detailed searching, they made use of the parallel, positive feedback and high accuracy of solution of ACO.…”
Section: ) Hybrid Si Algorithmsmentioning
confidence: 99%
“…Each SI technique has its own unique properties and will have different effects in different application scenarios. In recent years, in order to improve the performance of various SI techniques, and further improve the quality of the solution, various hybrid SI techniques: PSO-ACO [112]- [114], ACO-ABC [115], [116], DE-ABC [117], [118], FA-DE [119], PSO-DE [120], [121] and other hybrid SI algorithms [122], [123] are proposed and successfully applied in various fields. Reference [112] proposes a two-stage hybrid swarm intelligence optimization algorithm, using the randomicity, rapidity and wholeness of PSO and GA for rough searching; and for detailed searching, they made use of the parallel, positive feedback and high accuracy of solution of ACO.…”
Section: ) Hybrid Si Algorithmsmentioning
confidence: 99%
“…A set of 10 benchmark programs are used for the empirical study of the suggested approach and the study concludes that the suggested approach works better than random search, GA and PSO algorithm for the same set of programs on several parameters like the number of generation, average coverage, and ANOVA test. Varshney and Mehrotra [22]used a combination of PSO and differential Evolution to generate test data for structural testing. This suggested approach is used for data flow testing with the help of neighborhood search strategy for improvement in the performance of the suggested hybrid algorithm.…”
Section: A Pso In Structural Testingmentioning
confidence: 99%
“…Among them, heuristic search method generates an optimal test case based on the test adequacy criteria, including particle swarm optimization(PSO), genetic algorithm(GA), simulated annealing algorithm(SA), ant colony optimization(ACO), etc., of which PSO and GA are most widely used. For example Varshney [6] combined particle swarm algorithm and differential evolution algorithm and introduced a neighborhood search strategy. Bao [7] et al propose an improved genetic algorithm IAGA to improve the search performance in terms of early convergence by dynamically adjusting the parameters in each iteration according to the differences in individual similarity and fitness values.…”
Section: Introductionmentioning
confidence: 99%